Leadership in Action : Issues and Observations - Leaders who Encourage Get Their Mojo Working - Yarborough, J. Preston (Center for Creative Leadership, 2006)
Encouragement focuses on the present and on what someone is doing, without comparison to the actions of others, and it communicates appreciation for someone's abilities.